The determinants of micro, small, and medium entrepreneurial behavior to use social media: Technology-organization-environment framework - Nurbasari, Anny; Aribowo, Agus; Hadianto, Bram; Karim, Zulkefly Abdul; Raharjo, Medy Syari Khalifah Anggari (International Journal of Management and Sustainability, 2025)
Micro, small, and medium-sized businesses (MSMEs) in Indonesia have adopted digital technology at a much faster pace as a result of the COVID-19 epidemic, especially when it comes to using social media for marketing and communication. This study aims to investigate these factors using the Technology-Organization-Environment (TOE) framework, focusing on the post-COVID-19 period. A total of 255 business owners from 38 provinces in Indonesia were selected through snowball sampling to participate in the study. Data was collected via a structured questionnaire survey, and the proposed hypotheses were analyzed using SmartPLS 4.0, a variance-based structural equation modeling (SEM) software. The findings indicate that technological, organizational, and environmental factors significantly influence the intention to use social media (IUSM). These factors highlight the importance of understanding the role of technology, organizational readiness, and external pressures in shaping the decision of SMEs to adopt digital tools. Additionally, the study confirms that IUSM has a positive and significant effect on the actual social media utilization (SMU) among Indonesian SMEs. Based on these findings, it is recommended that SMEs conduct training programs to help strengthen their internal capabilities, making them better equipped to manage their online presence and customer interactions effectively.